2021
DOI: 10.1007/s11469-020-00482-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Associated with Alcohol and/or Substance Use During the COVID-19 Pandemic

Abstract: This study explored the relationship between alcohol and substance use in the general population during the early stages of COVID-19 as related to individual, family, and community stressors. A convenience sample of adults who resided in the USA and Canada was utilized. An online survey was conducted. Over one-third of the sample reported utilizing alcohol and substances as a means to cope during the pandemic. A linear regression revealed that use of social media as a source of information, being personally af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 42 publications
2
28
1
1
Order By: Relevance
“…We identified that approximately 12% of secondary school students in our sample reported substance-related coping using at least one of alcohol, cannabis, cigarettes, or vaping which also accounted for between 25-50% of students who used substances more generally. While the prevalence of substance-related coping in our youth sample is lower than what was recently observed within adult samples ( Cho et al, 2021 , MacMillan et al, 2021 ), it remains a concern that a significant portion of youth in Canada were relying on substance use as a strategy for coping with changes brought forth by the pandemic, particularly given the added substance accessibility challenges youth may have face during the early months of the lockdown, compared to adults. We also found that youth with generally poorer mental health – particularly those experiencing greater levels of depressive symptoms – were more likely to engage in substance-related coping.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…We identified that approximately 12% of secondary school students in our sample reported substance-related coping using at least one of alcohol, cannabis, cigarettes, or vaping which also accounted for between 25-50% of students who used substances more generally. While the prevalence of substance-related coping in our youth sample is lower than what was recently observed within adult samples ( Cho et al, 2021 , MacMillan et al, 2021 ), it remains a concern that a significant portion of youth in Canada were relying on substance use as a strategy for coping with changes brought forth by the pandemic, particularly given the added substance accessibility challenges youth may have face during the early months of the lockdown, compared to adults. We also found that youth with generally poorer mental health – particularly those experiencing greater levels of depressive symptoms – were more likely to engage in substance-related coping.…”
Section: Discussioncontrasting
confidence: 75%
“…Trends of increased substance use during the COVID-19 pandemic have been noted among both adults (Canadian Centre on Substance Use and Addiction, 2020; MacMillan et al, 2021 , Ornell et al, 2020 ) and youth ( Dumas et al, 2020 , Lechner et al, 2020 ). In a sample of Canadian adolescents, Dumas and colleagues ( Dumas et al, 2020 ) reported that while the total proportion of respondents who reported substance use decreased after COVID-19 physical distancing practices had taken place, those that reported using alcohol and cannabis had done so more frequently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicides were reported across the world both in developed and developing countries, across the general population and among health care professionals ( Thakur and Jain, 2020 ). In addition, there have been reports reporting increased rates of alcohol use, domestic violence and child abuse during pandemic that potentially increase vulnerability to suicide ( Campbell, 2020 , Green, 2020 , MacMillan et al, 2021 ).…”
Section: Pandemic Wavementioning
confidence: 99%
“…However, the WHO [ 15 ] warned of an “infodemic” in the age of COVID-19, described as “an over-abundance of information–some accurate and some not–that makes it hard for people to find trustworthy sources and reliable guidance when they need it.” A study among a Chinese population showed that this increase in social media exposure during the COVID-19 outbreak correlated with an increase in anxiety and depression [ 16 ]. The use of social media as a source of information about the pandemic was also associated with using alcohol and other substances as a means to cope [ 17 ]. Alcohol-related content has long been prevalent on social media platforms [ 18 ], as evident by the trending hashtag #quarantini during the early days of the pandemic [ 19 ].…”
Section: Introductionmentioning
confidence: 99%